Ionization and NO production in the polar mesosphere during high-speed solar wind streams: model validation and comparison with NO enhancements observed by Odin-SMR - S. Kirkwood; A. Osepian; E. Belova; J. Urban; K. Pérot; A. K. Sinha (Annales Geophysicae, 2015)
Precipitation of high-energy electrons (EEP) into the polar middle atmosphere is a potential source of significant production of odd nitrogen, which may play a role in stratospheric ozone destruction and in perturbing large-scale atmospheric circulation patterns. High-speed streams of solar wind (HSS) are a major source of energization and precipitation of electrons from the Earth's radiation belts, but it remains to be determined whether these electrons make a significant contribution to the odd-nitrogen budget in the middle atmosphere when compared to production by solar protons or by lower-energy (auroral) electrons at higher altitudes, with subsequent downward transport. Satellite observations of EEP are available, but their accuracy is not well established. Studies of the ionization of the atmosphere in response to EEP, in terms of cosmic-noise absorption (CNA), have indicated an unexplained seasonal variation in HSS-related effects and have suggested possible order-of-magnitude underestimates of the EEP fluxes by the satellite observations in some circumstances. Here we use a model of ionization by EEP coupled with an ion chemistry model to show that published average EEP fluxes, during HSS events, from satellite measurements (Meredith et al., 2011), are fully consistent with the published average CNA response (Kavanagh et al., 2012). The seasonal variation of CNA response can be explained by ion chemistry with no need for any seasonal variation in EEP. Average EEP fluxes are used to estimate production rate profiles of nitric oxide between 60 and 100 km heights over Antarctica for a series of unusually well separated HSS events in austral winter 2010. These are compared to observations of changes in nitric oxide during the events, made by the sub-millimetre microwave radiometer on the Odin spacecraft. The observations show strong increases of nitric oxide amounts between 75 and 90 km heights, at all latitudes poleward of 60° S, about 10 days after the arrival of the HSS. These are of the same order of ...